Effects of positive end-expiratory pressure on cerebral hemodynamics in acute brain injury patients - Giardina, Alberto; Cardim, Danilo; Ciliberti, Pietro; Battaglini, Denise; Ball, Lorenzo; Kasprowicz, Magdalena; Beqiri, Erta; Smielewski, Peter; Czosnyka, Marek; Frisvold, Shirin; Groznik, Matjaž; Pelosi, Paolo; et al. (Frontiers in Physiology, 2023)
Background: Cerebral autoregulation is the mechanism that allows to maintain the stability of cerebral blood flow despite changes in cerebral perfusion pressure. Maneuvers which increase intrathoracic pressure such as the application of positive end-expiratory pressure (PEEP) have been always challenged in brain injured patients for the risk of increasing intracranial pressure (ICP) and altering autoregulation. The primary aim of this study is to assess the effect of PEEP increase (from 5 to 15 cmH2O) on cerebral autoregulation. Secondary aims include the effect of PEEP increase on ICP and cerebral oxygenation. Material and Methods: Prospective, observational study including adult mechanically ventilated patients with acute brain injury requiring invasive ICP monitoring and undergoing multimodal neuromonitoring including ICP, cerebral perfusion pressure (CPP) and cerebral oxygenation parameters obtained with near-infrared spectroscopy (NIRS) and an index which expresses cerebral autoregulation (PRx). Additionally, values of arterial blood gases were analyzed at PEEP 5 and 15 cmH2O. Results are expressed as median (interquartile range). Results: Twenty-five patients were included in this study. The median age was 65 years (46-73). PEEP increase from 5 to 15 cmH2O did not lead to worsened autoregulation (PRx, from 0.17 (-0.003-0.28) to 0.18 (0.01-0.24), p=0.83). Although ICP and CPP changed significantly ((ICP from 11.11 (6.73-15.63) to 13.43 (6.8- 16.87) mm Hg, p=0.003 and CPP: 72.94 (59.19-84) to 66.22 (58.91-78.41) mm Hg, p=0.004), these parameters did not reach clinically relevant levels. No significant changes in cerebral oxygenation parameters were observed. Conclusion: Slow and gradual increases of PEEP did not alter cerebral autoregulation, ICP, CPP and cerebral oxygenation to levels triggering clinical interventions in acute brain injury patients.